Environmental impact assessment of multi-source solid waste based on a life cycle assessment, principal component analysis, and random forest algorithm. (1st August 2023) - Chen, Sichen; Yu, Lu; Zhang, Chenmu; Wu, Yufeng; Li, Tianyou
Abstract: As a national pilot city for solid waste disposal and resource reuse, Dongguan in Guangdong Province aims to vigorously promote the high-value utilization of solid waste and contribute to the sustainable development of the Greater Bay Area. In this study, life cycle assessment (LCA) coupled with principal component analysis (PCA) and the random forest (RF) algorithm was applied to assess the environmental impact of multi-source solid waste disposal technologies to guide the environmental protection direction. In order to improve the technical efficiency and reduce pollution emissions, some advanced technologies including carbothermal reduction‒oxygen-enriched side blowing, directional depolymerization‒flocculation demulsification, anaerobic digestion and incineration power generation, were applied for treating inorganic waste, organic waste, kitchen waste and household waste in the park. Based on the improved techniques, we proposed a cyclic model for multi-source solid waste disposal. Results of the combined LCA-PCA-RF calculation indicated that the key environmental load type was human toxicity potential (HTP), came from the technical units of carbothermal reduction and oxygen-enriched side blowing. Compared to the improved one, the cyclic model was proved to reduce material and energy inputs by 66%–85% and the pollution emissions by 15%–88%. To sum up, the environmental impact assessment and systematic comparison suggest a cyclic mode for multi-source solid waste treatments in the park, which could be promoted and contributed to the green and low-carbon development of the city. Highlights: LCA, PCA, and RF methods are coupled to evaluate the environmental impacts of multi-source solid waste treatment. Human toxicity potential was the key environmental load within the recycling park. Cyclic model provides enhanced energy conservation and emission reduction ability.